Iron Supplement Tablet Consumption is Associated with Hemoglobin Levels in Pregnant Women - Dwijayanti, Indah; Kuswati, Kuswati; Istikhomah, Henik (Poltekkes Kemenkes Surakarta, 2024)
Background: Hemoglobin (Hb) levels in pregnant women are checked in the first trimester (Hb1) and third trimester (Hb2). Hemoglobin requires iron (Fe) and protein; consumption of at least 90 iron tablets during pregnancy is recommended to increase Hb and prevent anemia. The purpose of this study was to analyze TTD consumption, hemoglobin levels in the first and third trimesters, and the relationship between TTD consumption and Hb levels in pregnant women at the Bayat Community Health Center, Klaten Regency. Methods: This was an associative quantitative study with a sample of 52 pregnant women in their third trimester who had their Hb checked at the Bayat Community Health Center in October 2022 (incidental sampling). Univariate and bivariate analyses were performed; the relationship between TTD consumption and Hb was tested using Spearman's correlation using IBM SPSS Statistics 23. Results: A total of 59.6% of respondents regularly consumed ≥90 TTD tablets, but 65.4% did not experience an increase in Hb levels from Hb1 to Hb2. Spearman's test showed a significant relationship between TTD consumption and Hb levels (p = 0.000; r = 0.516) with a positive direction, indicating that regular TTD consumption is associated with an increase in Hb levels. Conclusion: There is a moderate positive correlation between iron supplement consumption and hemoglobin levels in pregnant women at the Bayat Community Health Center. It is recommended to improve program interventions: strengthening counseling and education on iron supplement consumption compliance, monitoring compliance by health workers, providing adequate supplements, and conducting periodic Hb checks and follow-ups for mothers who do not show an increase in Hb.